GLUEBALLS AND TOPOLOGY IN LATTICE QCD WITH 2 LIGHT FLAVORS - Bitar, K; Edwards, R; Heller, U; Kennedy, A; Degrand, T; Gottlieb, S; Krasnitz, A; Kogut, J; Renken, R; Liu, W; Rossi, P; Ogilvie, M; et al. (1991)
We obtain estimates of the lightest glueball masses, the string tension, and the topological susceptibility in an exploratory study of QCD with two light flavors of quarks. Our calculations are performed at =5.6 with staggered quark masses mq=0.010 and 0.025 and on lattices ranging from 124 to 164. Our estimates suggest that, just as in the pure gauge theory, the 0++ is the lightest glueball with the 2++ about 50% heavier. Our mq=0.01 results predict a 0++ glueball mass of about 1.6 times the mass and the square root of the string tension of about 0.48 times the mass, which is surprisingly close to the usual phenomenologically motivated estimates of around 0.55. Our value of the topological susceptibility at mq=0.01 is consistent with the prediction, to O(mq) of the standard anomalous Ward identity. However, the variation of this susceptibility between mq=0.01 and mq=0.025 is weaker than the linear dependence one expects at small mq in the broken-chiral-symmetry phase of QCD. © 1991 The American Physical Society.